Interpreting audiences : the ethnography of media consumption - Moores, Shaun (Media, culture, and society series., 1993)
Interpreting audiences offers a comprehensive guide to important new developments in the study of media reception. Reviewing a wide range of work done by qualitative audience researchers over recent years, the author charts the emergence of a critical ethnographic perspective on everyday consumer practices.